Evaluation of the Use of Learning Management Systems on Herbal Medicine Topics based on the Level of User Satisfaction and Increased Knowledge - Firdaus; Zulharman; Augyera Reinatasya Seandrio (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The learning management system is a platform that helps deliver content online for learning purposes. Not all students can study herbal medicine in the Faculty of Medicine, University of Riau elective block. Thus, LMS as a forum for students to carry out independent learning needs to be evaluated. This study aims to determine the success of the LM S developed on the topic of herbal medicine based on the level of user satisfaction and increased knowledge. The research design was pre-experimental pretest posttest design with sequential explanatory mix-method. Respondents in this study were 2020 class students at the Faculty of Medicine, University of Riau, totaling 87 people using a random sampling technique. Based on the level of user satisfaction with the developed LMS, no users stated that they were very dissatisfied or dissatisfied, while 4 (5%) users stated that they were quite satisfied, 27 (31%) were satisfied, and 56 (64%) were very satisfied.The average pretest score was 41, and the average post-test score was 50. The test results of the difference between pretest and post-test values using the Wilcoxon test showed a difference with a sig (2-tailed) of 0.005 (p ≤ 0.05). The advantages of LMS are obtained from the aspects of content, accuracy, format, easy of use, and timeliness. Meanwhile, deficiencies found in the timing that the user feels were inconsistent with the amount of material presented. The developed learning management system has been successful and can improve students’ understanding.